Future directions in regulatory affairs - Chisholm, Orin; Critchley, Helen (Frontiers in Medicine, 2023)
The field of regulatory affairs deals with the regulatory requirements for marketing authorisation of therapeutic products. This field is facing a myriad of forces impacting all aspects of the development, regulation and value proposition of new therapeutic products. Changes in global megatrends, such as geopolitical shifts and the rise of the green economy, have emphasised the importance of manufacturing and supply chain security, and reducing the environmental impacts of product development. Rapid changes due to advances in science, digital disruption, a renewed focus on the centrality of the patient in all stages of therapeutic product development and greater collaboration between national regulatory authorities have been accelerated by the COVID-19 pandemic. This article will discuss the various trends that are impacting the development of new therapies for alleviating disease and how these trends therefore impact on the role of the regulatory affairs professional. We provide insights for the regulatory professional to remain at the forefront of these trends and prepare for their impacts on their work.